(Re-)Inventio Die Neuauflage als kreative Praxis in der nordalpinen Druckgraphik der Frühen Neuzeit - Hammami, Mariam; Pawlak, Anna; Rüth, Sophie (Andere Ästhetik - Studien, 2022)
This volume examines the making of new edition prints in the early modern north Alpine region and argues that it was a complex aesthetic strategy of creative appropriation.